2021
DOI: 10.7717/peerj.11014
|View full text |Cite
|
Sign up to set email alerts
|

Determining insulin sensitivity from glucose tolerance tests in Iberian and landrace pigs

Abstract: As insulin sensitivity may help to explain divergences in growth and body composition between native and modern breeds, metabolic responses to glucose infusion were measured using an intra-arterial glucose tolerance test (IAGTT). Iberian (n = 4) and Landrace (n = 5) barrows (47.0 ± 1.2 kg body weight (BW)), fitted with a permanent carotid artery catheter were injected with glucose (500 mg/kg BW) and blood samples collected at -10, 0, 5, 10, 15, 20, 25, 30, 45, 60, 90, 120 and 180 min following glucose infusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Interestingly, our findings were in direct contrast with other studies about other high-yield sows ( 24 26 ), implying that the Tibetan sows might have no or limited insulin resistance in the late gestation period. We speculated that Tibetan pigs, as lean pigs, had higher insulin sensitivity or stronger glucose tolerance than other obese pig breeds, which can be supported by previous reports that lean pigs had higher insulin sensitivity and glucose tolerance than obese pigs ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, our findings were in direct contrast with other studies about other high-yield sows ( 24 26 ), implying that the Tibetan sows might have no or limited insulin resistance in the late gestation period. We speculated that Tibetan pigs, as lean pigs, had higher insulin sensitivity or stronger glucose tolerance than other obese pig breeds, which can be supported by previous reports that lean pigs had higher insulin sensitivity and glucose tolerance than obese pigs ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 67%
“…For IVGTT data, insulin sensitivity index was calculated using a non-linear mixed effect approach for minimal model-derived insulin sensitivity index (SI) and glucose-mediated glucose clearance (SG) [29,30]. Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated based on fasting glucose and insulin values from the IVGTT according to the following formula: HOMA-IR = fasting plasma glucose [mM] x fasting plasma insulin [μU/ml]/ 22.5 [31]. The Matsuda insulin sensitivity index [32] was calculated for the IVGTT using time 0, 30, 60 and 120 minutes.…”
Section: Calculations and Statisticsmentioning
confidence: 99%
“…Some studies have reported greater postprandial serum levels of insulin in obese pig lines than in lean lines 15,16 , and others have reported different insulin sensitivities between these lines 17 . For example, Iberian pigs, which are considered an obese genetic line had lower whole-body insulin sensitivity but increased β-cell function compared with lean Landrace pigs 17 .…”
mentioning
confidence: 99%
“…Some studies have reported greater postprandial serum levels of insulin in obese pig lines than in lean lines 15,16 , and others have reported different insulin sensitivities between these lines 17 . For example, Iberian pigs, which are considered an obese genetic line had lower whole-body insulin sensitivity but increased β-cell function compared with lean Landrace pigs 17 . Although insulin sensitivity has been considered when comparing insulin responses between breeds, little is known about the relationship of insulin sensitivity with the observed variations Trial 1.…”
mentioning
confidence: 99%